Implementasi Sistem Pendaftaran Antrean Online melalui Mobile JKN dalam Pemenuhan Hak Pasien Atas Pelayanan Kesehatan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Digital transformation in the healthcare sector has encouraged the implementation of the Mobile JKN online registration system as an effort to improve healthcare services and fulfill patients’ rights. This system functions not only as an administrative innovation but also as a legal policy instrument to provide effective, efficient, and accessible healthcare services. This study aims to analyze the legal framework, implementation, and legal challenges of the Mobile JKN online registration system in fulfilling patients’ rights to healthcare services. This research employs normative legal research using a statutory approach and a conceptual approach. Legal materials consist of primary, secondary, and tertiary sources analyzed qualitatively through a descriptive analytical method. The results show that the implementation of Mobile JKN online registration is supported by several legal regulations, including the 1945 Constitution of the Republic of Indonesia, Law Number 17 of 2023 on Health, Presidential Regulation Number 59 of 2024, Minister of Health Regulation Number 24 of 2022 on Medical Records, and Minister of Health Regulation Number 6 of 2026 on Hospitals. The system improves service accessibility, administrative efficiency, service certainty, and supports the integration of Hospital Management Information Systems and Electronic Medical Records. However, the absence of specific regulations governing Mobile JKN online registration standards creates challenges related to personal data protection, health information system interoperability, digital infrastructure readiness, and public digital literacy. Therefore, strengthening digital healthcare regulations and governance is necessary to ensure legal certainty and protect patients’ rights.